Immittance response of CaSnO3 prepared by self-heat-sustained reaction - Azad, A.-M.; Shyan, L.L.W.; Alim, M.A. (Kluwer Academic Publishers, 1999)
The potential of CaSnO3 for application as a capacitor component possessing a small temperature coefficient of capacitance has been examined by ac small-signal measurements at elevated temperatures (25-300°C) in the frequency range 5-13 MHz. The samples were synthesized by a novel technique called self-heat-sustained (SHS) reaction. The ac data were acquired for the CaSnO3 samples sintered at various temperatures with varying soak temperatures, T, and some times, t (1200°C ≤ T ≤ 1600°C; 2 h ≤ t ≤ 8 h). An analysis of the electrical data in more than one complex-plane formalism indicated relaxation processes. The resistance of these sintered samples was dominated by the grain boundaries, and the capacitance exhibited near-linear behavior at elevated temperature for several decades of measurement frequency. The electrical behavior has been correlated with the evolved microstructure in these samples in conjunction with the results obtained in a previous study for solid-state reaction (SSR) derived sintered bodies. The multi-plane analytical criteria provided a meaning for the lumped equivalent circuit representation including the origin and purpose of the contributing elements extracted from each complex plane formalism.